English Result. Elementary: Workbook - McKenna J. Joe (Oxford, Oxford University Press, 2012)
Workbook with MultiROM Pack includes:- One page of grammar, vocabulary, and pronunciation practice for each lesson (with can do self-assessment)- Two pages of Skills practice - reading, writing, listening - for every unit Self check tests for every unit to help you measure your progress Student's MultiROM with interactive listening, vocabulary, and pronunciation practice, plus downloadable self-study documents Includes a free online practice test from oxfordenglishtesting.com.